Magdolna Jákfalvi, ed. “A performativitás mint fordulat” (Performativity as a Turn). Filológiai Közlöny (Philological Review) 62.4 (2016): 261-445. - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2016)
Since the “performative turn,” which dates back to the 1960s following John L. Austin’s presentation of findings about the performative power of speech acts in 1955, this phenomenon, Magdolna Jákfalvi claims in her preface as editor to this journal issue, has been the object of ongoing research and became an effective tool of literary interpretation, and later a norm of analysis (262). Indeed, while they have been in use for a considerable time, the terms performative and performativity are somewhat protean, their meanings likely to change when applied to the study of different aspects and domains of cultural life and practices. Most of the essays collected here under the title “Performativity as a Turn,” Jákfalvi adds, draw on a conference held in Budapest in May 2016, which purported to explore manifestations of the performative as well as to demonstrate the visibility and test the uses of the term in critical discourse. Understandably, a reconsideration of the meanings of performative and performativity is spreading, overtly or covertly, and to varying degrees, as a kind of fil rouge across the essays of the collection. Jákfalvi has divided the remarkable wealth of the material, altogether thirteen essays to be included in three groups, which are provided with the headings “Performatív elméleti paradigmák” (Theoretical paradigms of the performative), “Performatív realitás” (Performative reality), and “Performatív textualitás” (Performative textuality) respectively.